A new PNA-FISH probe targeting Fannyhessea vaginae - Sousa, Lúcia Filipa Guimarães Vieira (2021)
The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/fcimb.2021.779376/full#supplementary-material